Self etching adhesive on intact enamel - G M Devarasa; V V Subba Reddy; N L Chaitra (Wolters Kluwer Medknow Publications, 2012)
Background and Objective: to analyze the poor performance of self-etch adhesives on intact enamel. Materials and Methods: labial surfaces of 20 caries free permanent upper central and lateral incisors were cleaned, sectioned of their roots. All specimens were mounted on acrylic block and divided randomly into two groups. In one group the application of self-etch adhesive was carried as per manufacturer's instructions, composite cylinders were built, whereas in the other group, 37% phosphoric acid was applied before the application of self-etching adhesives. Then the resin tags were analyzed using the scanning electron microscope. Results: showed that when phosphoric acid was used, there was significant increase in the depth of penetration of resin tags. Conclusion: the results indicate that out of both treatment groups, pre-etching the intact enamel with 37% phosphoric acid resulted in the formation of longer resin tags and higher depth of penetration of resin tags of the Clearfil SE bond, which might have resulted in attaining higher bond strength of the Clearfil SE bond to intact enamel.